Thermodynamics of nanobody binding to lactose permease - Hariharan, Parameswaran (Biochemistry, 2016)
Camelid nanobodies (Nbs) raised against the outward-facing conformer of a double-Trp mutant of the lactose permease of Escherichia coli (LacY) stabilize the permease in outward-facing conformations. Isothermal titration calorimetry is applied herein to dissect the binding thermodynamics of two Nbs, one that markedly increases access to the sugar-binding site and another that dramatically increases affinity for galactoside. The findings presented here show that both enthalpy and entropy contribute favorably to binding of the Nbs to WT LacY and that Nb binding to double-Trp mutant G46W/G262W is driven by greater enthalpy at an entropic penalty. Thermodynamic analyses support the interpretation that WT LacY is stabilized in outward-facing conformations similar to the double-Trp mutant with closure of the water-filled cytoplasmic cavity through conformational selection. The LacY conformational transition required for ligand binding is reflected by a favorable entropy increase. Molecular dynamics simulations further suggest that the entropy increase likely stems from release of immobilized water molecules primarily from the cytoplasmic cavity upon closure.